Serious Complications Related to Obstetric Anesthesia. Issue 3 (September 2015) - D'Angelo, R.; Smiley, R.M.; Riley, E.T.; Segal, S.
<x xml:space="preserve">Abstract</x> (Anesthesiology. 2014; 120:1505–1512)